Anti-adhesion uranium extraction fiber and preparation method and performance evaluation method thereof
By grafting PEI-AO functional groups and IBOMA onto hemp fiber, the challenges of uranium adsorption selectivity and marine biofouling are addressed, achieving high uranium adsorption capacity and resistance to fouling organisms.
Patent Information
- Application Number
- CN202411338054.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
AI Technical Summary
Hemp fiber exhibits poor uranium adsorption selectivity and is prone to marine biofouling, lacking comprehensive evaluation methods for antifouling performance, which hinders effective uranium extraction from seawater.
A method involving grafting PEI-AO functional groups and IBOMA onto hemp fiber through chemical reactions and ultraviolet irradiation to enhance adsorption capacity and resistance to fouling organisms, combined with a performance evaluation method using Diplophysarum and Diplococcus spp. as model organisms.
The modified hemp fiber demonstrates high uranium adsorption capacity and resistance to marine fouling, maintaining effective uranium extraction despite the presence of seaweed and bacteria, with improved anti-algae and antibacterial properties.
Smart Images

Figure CN119221289A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of new materials, and in particular to an anti-adhesion uranium extraction fiber and a preparation method and a performance evaluation method thereof. Background Art
[0002] Long-term sustainable global energy supply has become one of the most serious challenges facing human society. With the rapid development of the nuclear industry, the demand for uranium fuel is increasing. However, as a naturally occurring element, the currently available terrestrial uranium reserves will be exhausted within the next 100 years. It is estimated that the uranium reserves dissolved in the ocean are 1000 times that of terrestrial ores. Therefore, the selective ultrafast extraction of uranyl ions (UO2 2+ ) is of great strategic significance for ensuring the fuel supply for sustainable nuclear energy production in the future. However, the conditions in seawater are complex, and the abundant marine organisms will have a negative impact on the adsorbent, which in turn makes it difficult to extract uranium from seawater. Therefore, it is necessary to design uranium adsorbents that have both adsorption and antifouling properties with resistance to biofouling, high affinity and selectivity, high adsorption capacity and reusability.
[0003] Hemp fiber (HF) is one of the largest plant fibers and one of the most promising biosorbent biomaterials. In the past decade, people have shown great interest in hemp-based biosorbents. As a new type of biomass material, hemp fiber is not only inexpensive and green, but also has good biocompatibility, chemical and physical stability, and resistance to toxic metal ions. Hemp fiber is mainly composed of three main components, namely cellulose, hemicellulose and lignin, among which cellulose is considered to be the main skeleton component of the fiber structure. Cellulose is covered with hemicellulose and lignin components, and provides strength, stiffness and structural stability to the fiber. Because its surface is rich in a large number of hydrophilic groups, such as hydroxyl and carboxyl groups, it has good hydrophilicity and is suitable for water environments. Through chemical modification, it can be made into a seawater uranium extraction adsorption material with good application prospects.
[0004] At present, there are problems in the application of hemp fiber as uranium adsorption material:
[0005] Hemp fiber itself has poor adsorption performance. There are only some hydroxyl and carboxyl groups on the surface of hemp fiber, and the adsorption selectivity for uranium is weak. However, by grafting effective functional groups, the adsorption capacity and adsorption selectivity will be greatly improved. At the same time, in order to meet the needs of real marine applications, it is necessary to give hemp fiber the ability to resist marine biofouling while ensuring excellent adsorption performance. Therefore, how to construct hemp fiber with both adsorption and anti-fouling properties, and how to comprehensively evaluate the adsorption and anti-fouling properties of fiber materials are the key points.
[0006] At present, the evaluation of the antifouling performance of fiber adsorbent materials is mostly limited to the study of their antibacterial properties. However, there are typical fouling organisms such as diatoms in seawater. Therefore, it is not comprehensive to evaluate the antifouling performance of fiber adsorbent materials only by antibacterial properties. There is no detailed and unified anti-algae evaluation method for fiber adsorbent materials in the reported studies. Therefore, it is necessary to establish a research method for the anti-algae performance of fiber adsorbent materials.
[0007] At the same time, the performance evaluation of uranium adsorption materials should also consider the impact of fouling organisms on the adsorption process. Most of the existing studies on uranium adsorption materials put the test materials into uranium solutions or simulated seawater to study their uranium adsorption performance, but this is very different from the actual sea application environment. There are a large number of fouling organisms in the actual marine environment, such as bacteria, seaweed, mussels, etc. After being placed in the real sea, the fouling organisms will selectively attach to the surface of the material, hindering the effective contact between the active sites on the surface of the material and uranium, thereby reducing the adsorption effect of the material. Therefore, it is necessary to optimize the evaluation method of uranium adsorption performance, further study the adsorption performance of the material in uranium solutions containing fouling organisms or simulated seawater, and combine the adsorption performance and antifouling performance evaluation methods to screen and optimize the material, determine the optimal grafting rate of the adsorption functional group and the antifouling functional group, and ensure that the material has the maximum adsorption performance and the ability to resist the attachment of fouling organisms, making it more suitable for real sea applications. . Summary of the invention
[0008] In view of this, in order to solve the problem that uranium extraction fibers are easily attached by marine fouling organisms in actual sea deployment applications and cannot achieve a relatively ideal adsorption effect, and how to screen excellent fiber adsorption materials through appropriate adsorption and anti-fouling evaluation methods, the present invention provides an anti-attachment uranium extraction fiber and its preparation method and performance evaluation method.
[0009] The technical solutions adopted are:
[0010] A method for preparing an anti-adhesion uranium extraction fiber of the present invention comprises the following steps:
[0011] S1. Add acrylonitrile to the polyethyleneimine solution and mix well to obtain a polyethyleneimine-acrylonitrile functional monomer;
[0012] S2. The hemp fiber after washing and drying is immersed in a polyethyleneimine-acrylonitrile functionalized monomer mixed solution, and N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added, soaked, washed and dried to obtain polyethyleneimine-acrylonitrile functionalized fiber;
[0013] S3. A mixed solution of hydroxylamine hydrochloride and sodium hydroxide is prepared, and polyethyleneimine - acrylonitrile functionalized fibers are added thereto. After sufficient reaction, the fibers are removed, washed and dried to obtain polyethyleneimine - amidoxime functionalized fibers.
[0014] S4. Using ethanol as solvent, trimethoxymercaptosilane coupling agent and isobornyl methacrylate are grafted by ultraviolet light irradiation; then the polyethyleneimine-amidoxime functionalized fiber is immersed in the mercaptosilane coupling agent and isobornyl methacrylate solution and soaked at room temperature for reaction; after washing and drying, the anti-adhesion uranium extraction fiber is obtained.
[0015] Furthermore, in step S1, polyethyleneimine is weighed and dissolved in water to obtain a polyethyleneimine solution, which is purged with nitrogen for 40-60 minutes at room temperature to remove oxygen; then acrylonitrile is added dropwise and stirred, and acrylonitrile is added to the polyethyleneimine solution and mixed evenly to obtain a polyethyleneimine-acrylonitrile functionalized monomer.
[0016] Furthermore, in step S2, the washed and dried hemp fiber is immersed in the polyethyleneimine-acrylonitrile functional monomer mixed solution in step S1, and N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added, and the pH of the solution is adjusted to 6-8.
[0017] Furthermore, in step S3, a mixed solution of hydroxylamine hydrochloride and sodium hydroxide is prepared, wherein the mixed solution of hydroxylamine hydrochloride and sodium hydroxide has a mass ratio of 1:0.5-1 and is dissolved in ethanol and deionized water; polyethyleneimine-acrylonitrile functionalized fiber is added thereto, and the reflux stirring conditions are 60-70°C for 20-24h; after cooling to room temperature, the sample is taken out, washed with deionized water several times, and dried at 50-60°C overnight to obtain polyethyleneimine-amidoxime functionalized fiber.
[0018] Furthermore, in step S4, trimethoxymercaptosilane coupling agent and isobornyl methacrylate are dissolved in ethanol, and then irradiated and grafted with ultraviolet lamp for 2-4 hours; then polyethyleneimine-amidoxime functionalized fiber is added thereto, and an appropriate amount of ethanol is added, and soaked at room temperature for 10-12 hours; finally, rinsed with deionized water several times, and then dried at 50-60°C for 20-24 hours, to obtain anti-adhesion uranium extraction fiber.
[0019] Furthermore, in step S4, the mass ratio of trimethoxymercaptosilane coupling agent to isobornyl methacrylate is (1-3):1.
[0020] Furthermore, in step S4, the mass ratio of polyethyleneimine-amidoxime functionalized fiber to isobornyl methacrylate is (0.5-3):1.
[0021] The anti-adhesion uranium extraction fiber of the present invention is prepared by the preparation method described in any of the above schemes.
[0022] A method for evaluating the antifouling performance of the anti-adhesion uranium extraction fiber of the present invention comprises the following steps:
[0023] Using Diplophysarum as a model fouling organism to evaluate anti-fouling performance, the sample was sterilized under ultraviolet light; when the algae cell concentration in the culture medium entered a stable period, the sterilized sample was placed in the cell culture medium for mixed culture, and the original fiber algae solution was selected as a control sample. The algae solution was observed using a fluorescence microscope at different time periods; the anti-algae rate of the fiber was calculated as follows:
[0024]
[0025] Among them, A represents the number of seaweed attached to the fiber, N, M1 and M2 represent the number of seaweed attached to the fiber, the scale length and the fiber length, respectively; B represents the anti-algae rate, A1 and A2 represent the number of seaweed attached to the surface of modified fiber and HF, respectively.
[0026] Furthermore, the anti-fouling performance of Diplococcus spp. was evaluated by using Diplococcus spp. as a model fouling organism. A sample of 0.01-0.02 g was weighed and placed under ultraviolet light for 15-20 min. The concentration of algae cells in the culture medium was stable for 10 5 ce ll / mL or above, the sterilized sample was placed in 30-50mL cell culture medium for mixed culture, the original fiber seaweed solution was selected as the control sample, and the fiber was observed using a fluorescence microscope within 2-7 days.
[0027] A method for evaluating the uranium adsorption performance of the anti-adhesion uranium extraction fiber of the present invention comprises the following steps:
[0028] The exponentially growing Amphiprion and Nitzschia closterium were added to simulated seawater containing uranium to obtain seawater containing algae liquid. The simulated seawater containing uranium was used as a control group for uranium adsorption experiments. Uranium adsorption experiments were carried out in seawater filtered with uranium and in unfiltered seawater.
[0029] Furthermore, when algae cells were added to simulated seawater with a uranium concentration of 1 mg / L to a concentration of 10 5 The culture liquid of Ampelopsis cerevisiae and Nitzschia closterii entered the stable period with a concentration of 1 mg / mL or more, and the seawater containing algae liquid was obtained; 1 mg / L simulated seawater was used as the control group for uranium adsorption experiments. Uranium adsorption experiments were carried out in filtered (bacteria-free) seawater with uranium (1 mg / L) and unfiltered seawater.
[0030] The technical solution of the present invention has the following characteristics:
[0031] Feature 1: The present invention introduces PEI-AO functional groups through amide condensation reaction to increase HF adsorption capacity and selectivity. The PEI-AN monomer is synthesized through Michael addition reaction, and then grafted onto the fiber through a one-step amide condensation reaction, and finally oxime is performed. The affinity of the amidoxime ligand is enhanced through the synergistic effect of the two ligands, which can ensure high adsorption capacity for uranyl, and has stronger hydrophilicity than single polyamidoxime.
[0032] Feature 2: Isoborneol methacrylate (IBOMA) is introduced on the fiber surface by irradiation grafting, which greatly improves the anti-biological fouling ability of HF. The natural herbal antibacterial borneol has excellent broad-spectrum antibacterial ability. The borneol-based polymer IBOMA has been shown to have strong anti-bacterial infection activity. The present invention uses a trimethoxymercaptosilane coupling agent and irradiation grafting on the fiber surface to give the fiber excellent antibacterial, anti-algae and anti-mussel capabilities. IBOMA is a hydrophobic anti-biological fouling functional group. The introduction of the hydrophobic functional group will greatly improve the anti-algae performance of HF, and the antibacterial performance will also be improved. It can ensure that fouling organisms in the ocean will not occupy the adsorption sites of the fiber, which is convenient for the recycling of adsorption materials and the construction of hemp fibers with both adsorption and anti-fouling properties.
[0033] Feature 3: The anti-algae performance of fiber adsorption materials is evaluated by fluorescence microscopy and the antibacterial performance is evaluated by plane counting method. The present invention uses Halamphoa sp. to test the anti-algae performance of hemp fiber uranium adsorption materials. After culturing in Halamphoa sp. for 2 days and 7 days, 3 fibers are randomly selected for photographing using a fluorescence microscope, and then the Halamphoa sp. attached to the fiber surface are selected for counting and the average value is taken. Escherichia coli (E.coli), Staphylococcus aureus (S.aureus) and Pseudoalteromonas marine (Pm) are selected for antibacterial performance evaluation, and the colonies on the solid culture medium are counted one by one using PS software, and samples close to the average value are selected for comparison with the original fiber, and the antibacterial rate is calculated.
[0034] Feature 4: The adsorption performance of the test material under the condition of fouling organisms is tested to investigate the influence of fouling organisms in the ocean on the material during the adsorption process. Diplophyte and Nitzschia closterii in the exponential growth period are added to simulated seawater with a uranium concentration of 1 mg / L to obtain seawater containing algae liquid. The presence of seaweed has little effect on the uranium capture ability of the HFPE I-AO@I BOMA prepared by the present invention. Its uranium adsorption amount in seawater containing Nitzschia closterii and Diplophyte for 48 hours (1803.1±155.6 and 1724.1±149.2μg / g) is close to that in seawater without algae (1985.4±175.5μg / g), indicating that it has good anti-algae ability in the process of extracting uranium from seawater. Uranium adsorption tests were conducted in filtered (bacteria-free) seawater with uranium (1 mg / L) and unfiltered seawater. Compared with filtered seawater, the adsorption capacity of uranium by HFPE I-AO in unfiltered seawater decreased from 1584.8 μg / g to 1102.1 μg / g, a significant decrease of 30.46%. The uranium adsorption capacity of HFPE I-AO@I BOMA decreased from 1487.6 μg / g to 1293 μg / g, a decrease of only 13.08%. This indicates that the adverse effects of marine bacteria have little effect on the uranium adsorption performance of HFPE I-AO@IBOMA.
[0035] The beneficial effects of the present invention are:
[0036] 1. The anti-adhesion uranium extraction fiber prepared by the present invention is a uranium extraction material with both high efficiency uranium adsorption capacity and resistance to marine fouling.
[0037] The antibacterial rate of the anti-adhesion uranium extraction fiber HFPEI-AO@IBOMA of the present invention is as high as 82.22%, and the anti-algae rate after 7 days is as high as 90.82%. It also has a significant anti-adhesion effect on large fouling organisms. At the same time, HFPE I-AO@IBOMA also shows excellent affinity for uranyl ions. d =5.4×10 4 mL / g, which is 17.3 times that of vanadium. The adsorption capacity in uranium-spiked Nitzschia closterium solution is as high as 1803.1μg / g, which is 1.3 times that of HFPE I-AO. Compared with seawater after uranium filtration (no bacteria), the uranium adsorption capacity of HFPE I-AO@I BOMA in unfiltered seawater decreased from 1487.6μg / g to 1293μg / g, a decrease of only 13.08%, while HFPE I-AO decreased by 30.46%. When the pH condition is close to that of seawater environment (≈8.0), the adsorption capacity of HFPEI-AO@I BOMA can reach more than 22 times that of HF.
[0038] 2. The present invention comprehensively considers the optimal ratio of the grafted adsorption group and the antifouling group. First, 4 ratios of PE I-AO are grafted to give hemp fiber excellent uranium adsorption performance, and the optimal ratio is selected by the highest uranium adsorption capacity at different pH. Secondly, on the basis of maximizing the uranium adsorption performance, 4 ratios of antifouling group I BOMA are grafted, and the optimal ratio is selected through the evaluation of antibacterial and anti-algae performance to achieve the effect of both adsorption performance and antifouling performance.
[0039] 3. The preparation process of the anti-adhesion uranium extraction fiber of the present invention is simple and easy to operate. The fiber matrix used is hemp fiber, which can effectively reduce economic costs. Hemp fiber is selected as the fiber matrix mainly because it has relatively good stability, has been commercialized, and has a low price.
[0040] 4. The anti-adhesion uranium extraction fiber of the present invention has high mechanical strength, is easy to separate and recover, is convenient for actual sea deployment, has relatively large practical application value, and the desorption efficiency after 5 adsorption and desorption cycles can reach more than 90%. Therefore, the anti-adhesion uranium extraction fiber of the present invention is easy to recycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The uranium adsorption capacity of the fiber-based uranium extraction adsorption material HFPEI-AO (3-8:10) prepared in Examples 2-5 of the present invention;
[0042] Figure 2 is the wetting time of the fiber-based uranium extraction adsorbent material of Example 1, Example 4 and Example 8 when the water droplet contacts the fiber-based uranium extraction adsorbent material of Example 1, Example 4 and Example 8;
[0043] Figure 3 The uranium adsorption capacity of the fiber-based uranium adsorption materials under different pH conditions in Example 1, Example 4 and Example 8;
[0044] Figure 4 K is the adsorption capacity of the fiber-based uranium adsorption material for different ions in Example 1 and Example 8 d value;
[0045] Figure 5 is the desorption efficiency of the anti-adhesion uranium extraction fiber of Example 8;
[0046] Figure 6 These are the anti-algae pictures of the fiber-based uranium extraction adsorption materials under a fluorescence microscope of Examples 1, 4 and 8;
[0047] Figure 7 The anti-algae rate of the fiber-based uranium extraction adsorption materials of Examples 1, 4 and 6-9 against Diplococephala;
[0048] Figure 8These are the antibacterial pictures of the fiber-based uranium extraction adsorption materials of Example 1, Example 4 and Example 8 against Escherichia coli, Staphylococcus aureus and marine bacteria;
[0049] Fig. 9 The antibacterial rates of the fiber-based uranium extraction adsorption materials of Examples 1, 4 and 6-9 against Escherichia coli, Staphylococcus aureus and marine bacteria;
[0050] Fig.10 The uranium adsorption capacity of the fiber-based uranium extraction adsorption material in uranium-spiked simulated seawater of Example 1, Example 4 and Example 8;
[0051] Fig.11 The uranium adsorption capacity of the fiber-based uranium extraction adsorbent material of Example 1, Example 4 and Example 8 in uranium-spiked B. rapae liquid for 48 hours;
[0052] Fig.12 The uranium adsorption capacity of the fiber-based uranium extraction adsorption material of Example 1, Example 4 and Example 8 in the uranium-spiked Nitzschia closterium liquid for 48 hours;
[0053] Fig.13 The uranium adsorption capacity of the fiber-based uranium adsorption materials of Example 4 and Example 8 in filtered seawater and unfiltered seawater for 48 hours. DETAILED DESCRIPTION
[0054] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0055] The following are the abbreviations and corresponding chemical names:
[0056] PEI: polyethyleneimine; AN: acrylonitrile; I BOMA: isobornyl methacrylate; AO: amidoxime;
[0057] HF: hemp fiber; HFPE I-AO@I BOMA: the anti-adhesion uranium extraction fiber of the present invention; HFPE I-AO: adsorption material.
[0058] Example 1
[0059] The hemp fiber was soaked in a 10% NaOH solution for two hours, then washed with deionized water for several times, and then dried in an oven at 60° C. to obtain hydroxylated modified HF.
[0060] Embodiment 2-5
[0061] S1. Weigh 2.0 g of polyethyleneimine (PEI) and dissolve it in 20 ml of water, and purge it with nitrogen for 60 min at room temperature to remove oxygen. Inject acrylonitrile (AN) dropwise, and stir the reaction mixture at 60 ° C for 12 h. Vacuum dry at 45 ° C for 24 h to remove residual monomers and solvents to obtain PEI-AN. Four PEI-ANs were prepared with [AN]- to -[N] molar ratios of 3:10, 5:10, 7:10 and 8:10, respectively referred to as PE I-AN-3, PE I-AN-5, PEI-AN-7 and PEI-AN-8, corresponding to Examples 2-5. The [AN]- to -[N] molar ratio is defined as the number of moles of AN divided by the number of moles of PEI repeating units (-CH2CH2NH-, with a molar mass of 43 g / mol).
[0062] S2. Weigh 0.12g N-hydroxysuccinimide and 0.22g 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and dissolve them in 50mL deionized water, then add the PEI-AN (3-8:10) and dissolve it completely. Adjust the pH value of the solution to 7.0 with HCl and NaOH. Then add 0.5g HF of Example 1 to the above solution and react at 25°C for 24h. After the reaction is completed, the obtained fiber is washed several times with deionized water and anhydrous ethanol and dried in an oven at 60°C overnight to prepare the adsorbent material HFPE I-AN (3-8:10).
[0063] S3. Dissolve 2.0 g NH2OH·HCl and 1.0 g NaOH in 90 mL ethanol and 10 mL deionized water by magnetic stirring. At the same time, transfer 3.0 g HFPEI-AN (3-8:10) and the above solution to a 250 mL three-necked flask and reflux and stir at 70 °C for 24 h. After cooling to room temperature, take out the sample, wash it several times with deionized water, and dry it at 60 °C to obtain the adsorption material HFPE I-AO (3-8:10).
[0064] S4. Weigh 7 portions of 0.02g of samples from Examples 2-5 respectively and place them in conical flasks for uranium adsorption performance test. Add 50mL of uranium solution with pH values of 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0 and a concentration of 100mg / L to each conical flask, and place them in a constant temperature oscillator at 120r / min for 12h. Take the supernatant to measure the uranium concentration. The results are as follows Figure 1As shown, at pH = 7.0, the adsorption capacity of the HFPE I-AO (7:10) adsorption material of Example 4 can reach 241.9 mg / g, which is higher than the adsorption capacity of Example 2 (206.6 mg / g), Example 3 (208.2 mg / g) and Example 5 (234.6 mg / g). Therefore, Example 3 has the best adsorption effect, and the HFPE I-AO mentioned below is HFPE I-AO (7:10).
[0065] Embodiment 6-9
[0066] S1. 3.0g trimethoxymercaptosilane coupling agent and 3.0g isobornyl methacrylate were dissolved in 50ml ethanol, and then irradiated with ultraviolet lamp for 4h. Then HFPE I-AO was added, and the mass ratio of HFPE I-AO to IBOMA was 3:1, 2:1, 1:1 and 1:2, corresponding to Examples 6-9, and an appropriate amount of ethanol was added, and soaked at room temperature for 12h. Finally, it was rinsed with deionized water several times, and then dried at 60℃ for 24h to obtain 4 ratios of anti-adhesion uranium extraction fiber HFPE I-AO@I BOMA.
[0067] S2. Anti-adhesion uranium extraction fiber performance test;
[0068] The anti-adhesion uranium extraction fiber obtained in this embodiment has I BOMA grafted on the surface of the adsorbent material, and its surface hydrophilicity will be reduced (e.g. Figure 2 ), having an anti-adhesion effect; within 7 days of co-culture with the double-browed algae, it showed a significant growth inhibition effect; the combined effect of the PE I group and the AO group made it close to the seawater pH, and the adsorption capacity was increased by more than 22 times compared with the HF in Example 1 (as shown in Figure 3 HFPE I-AO@IBOMA prepared in Example 8 under the condition of multi-ion coexistence 1:1 Shows excellent selectivity for uranium K d The value is more than 17 times that of vanadium (such as Figure 4 After 5 cycles of adsorption and desorption, the desorption efficiency can be maintained above 91% (as shown in Figure 5 The uranium adsorption capacity of the uranium spiked Nitzschia closterium solution was as high as 1803.1 μg / g, which is 1.3 times that of HFPE I-AO (as shown in Figure 2). Fig.12 Compared with seawater after uranium filtration (without bacteria), the uranium adsorption capacity of HFPE I-AO@I BOMA in unfiltered seawater decreased from 1487.6 μg / g to 1293 μg / g, a decrease of only 13.08%, while that of HFPE I-AO decreased by 30.46% (as shown in Figure 2 ). Fig.13 shown).
[0069] The anti-fouling performance test process is as follows:
[0070] The anti-fouling performance was evaluated by using the diaphanous algae as a model fouling organism; 0.02 g of the samples of Example 1, Example 3, and Examples 6-9 were weighed and sterilized under ultraviolet light for 15 min. 5 After the concentration of 11 / mL or more entered the stable period, the sterilized samples of Example 1, Example 3 and Examples 6-9 were placed in 50 mL of cell culture medium for mixed culture. The fiber seaweed solution of Example 1 was selected as a control sample. The fibers were observed using a fluorescence microscope at different time periods. The results are as follows: Figure 6 As shown in the figure, compared with the growth trend of the fiber seaweed in Example 1, the anti-adhesion uranium extraction fiber HFPE I-AO@IBOMA prepared in Example 8 1:1 After being co-cultured with seaweed for 7 days, it showed a significant growth inhibition effect, and the anti-algae rate could reach more than 90% ( Figure 7 As shown), therefore HFPE I-AO@I BOMA 1:1 The effect is the best. The calculation formula of the fiber's anti-algae rate is as follows:
[0071]
[0072] Among them, A represents the number of seaweed attached to the fiber, N, M1 and M2 represent the number of seaweed attached to the fiber in the picture, the ruler length and the fiber length, respectively. Among them, B represents the anti-algae rate, and A1 and A2 represent the number of seaweed attached to the surface of the modified fiber and HF, respectively.
[0073] The antibacterial experiment of the adsorption material was carried out with three kinds of bacteria, namely Escherichia coli (E.coli), Staphylococcus aureus (S.aureus) and Pseudoalteromonas marine (Pm). First, the samples of Example 1, Example 4 and Example 6-9 were irradiated under ultraviolet lamp (20W, 253.7nm) for 30min, and then transferred to a 150mL conical flask, 50mL of liquid culture medium and diluted E.coli or S.aureus or Pm were added, and then placed in an incubator and cultured at 37°C for 12h. After the culture is completed, the samples of Example 1, Example 4 and Example 6-9 are taken out, and the surface of the sample is rinsed with 10mL of liquid culture medium to rinse off the bacteria. Take 10μL of the above-mentioned liquid culture medium containing bacteria and transfer it to 10mL of freshly prepared liquid culture medium. After mixing evenly, take out 10μL of liquid culture medium and evenly apply it on the surface of the solid culture medium, and then culture the solid culture medium at 37°C for 24h. Take out the culture dish for photographing and counting ( Figure 8 As shown), taking Example 1 as the control sample, the samples of Examples 4 and Examples 6-9 showed obvious antibacterial effects, and the antibacterial rates of Examples 8 and 9 were both above 80% ( Fig. 9 shown).
[0074] The uranium adsorption performance test process is as follows:
[0075] The HF of Example 1 was used as a control sample for uranium adsorption performance; 7 portions of 0.02 g of the samples of Example 4, Example 8 and the control sample were weighed and placed in conical flasks for uranium adsorption performance testing. 50 mL of uranium solution with a pH of 3.0, 4.0, 5.0, 6.0, 7.0, 8.0 and 9.0 and a concentration of 100 mg / L was added to each conical flask, and the flasks were placed in a constant temperature oscillator and shaken at a speed of 120 r / min for 12 hours, and the supernatant was taken to determine the uranium concentration. The results are shown in FIG. Figure 3 As shown, when the pH value is close to 8.0 in the seawater environment, the anti-adhesion uranium extraction fiber HFPE I-AO@I BOMA prepared in Example 8 1:1 The adsorption capacity can reach 199.8 mg / g, which is much higher than the adsorption capacity of HF (11.6 mg / g).
[0076] The anti-fouling adsorption performance test process is as follows:
[0077] The effect of algae on uranium adsorption was studied to evaluate the antifouling performance of the material in the uranium capture process. The adsorption of uranium by the materials prepared in Example 1, Example 4 and Example 8 in simulated seawater spiked with uranium containing algae liquid and simulated seawater spiked with uranium without algae liquid was compared. Exponentially growing algae and small crescent-shaped nitzschia were added to simulated seawater with a uranium concentration of 1 mg / L to obtain seawater containing algae liquid. Figure 10-12 As shown, the presence of seaweed has little effect on the uranium capture ability of Example 8. Its uranium adsorption capacity in seawater containing Nitzschia closterium and Ampelopsis schrenkiana for 48 hours (1803.1±155.6 and 1724.1±149.2 μg / g) is close to that in seawater without algae (1985.4±175.5 μg / g), indicating that it has good anti-fouling ability in the process of uranium extraction from seawater.
[0078] The effect of marine bacteria on uranium adsorption properties was investigated to evaluate the antifouling properties of the material in the uranium capture process. Uranium adsorption tests were conducted in uranium-filtered (bacteria-free) and unfiltered seawater, such as Fig.13 As shown, compared with the filtered seawater, the adsorption capacity of uranium by HFPE I-AO prepared in Example 4 in unfiltered seawater decreased from 1584.8 μg / g to 1102.1 μg / g, a significant decrease of 30.46%. The uranium adsorption capacity of the sample HFPE I-AO@I BOMA prepared in Example 8 decreased from 1487.6 μg / g to 1293 μg / g, a decrease of only 13.08%. This indicates that the adverse effects of marine bacteria have little effect on the material HFPE I-AO@I BOMA prepared in Example 8.
[0079] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be interpreted as limiting the present invention itself. Various changes can be made to it in form and detail without departing from the spirit and scope of the present invention as defined in the appended claims. Any equivalent embodiments or changes made without departing from the spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing an anti-adhesion uranium extraction fiber, characterized in that: The steps include: S1. Add acrylonitrile to the polyethyleneimine solution and mix well to obtain a polyethyleneimine-acrylonitrile functional monomer; S2. The hemp fiber after washing and drying is immersed in a polyethyleneimine-acrylonitrile functionalized monomer mixed solution, and N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added, soaked, washed and dried to obtain polyethyleneimine-acrylonitrile functionalized fiber; S3. A mixed solution of hydroxylamine hydrochloride and sodium hydroxide is prepared, and polyethyleneimine - acrylonitrile functionalized fibers are added thereto. After sufficient reaction, the fibers are removed, washed and dried to obtain polyethyleneimine - amidoxime functionalized fibers. S4. Using ethanol as solvent, trimethoxymercaptosilane coupling agent and isobornyl methacrylate are grafted by ultraviolet light irradiation; then the polyethyleneimine-amidoxime functionalized fiber is immersed in the mercaptosilane coupling agent and isobornyl methacrylate solution and soaked at room temperature for reaction; after washing and drying, the anti-adhesion uranium extraction fiber is obtained.
2. The method for preparing the anti-adhesion uranium-extracting fiber according to claim 1, characterized in that: In step S1, polyethyleneimine is weighed and dissolved in water to obtain a polyethyleneimine solution, which is purged with nitrogen for 40-60 minutes at room temperature to remove oxygen; then acrylonitrile is added dropwise and stirred, and acrylonitrile is added to the polyethyleneimine solution and mixed evenly to obtain a polyethyleneimine-acrylonitrile functional monomer.
3. The method for preparing the anti-adhesion uranium-extracting fiber according to claim 1, characterized in that: In step S2, the washed and dried hemp fiber is immersed in the polyethyleneimine-acrylonitrile functional monomer mixed solution in step S1, and N-hydroxysuccinimide and 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride are added, and the pH of the solution is adjusted to 6-8.
4. The method for preparing the anti-adhesion uranium-extracting fiber according to claim 1, characterized in that: In step S3, a mixed solution of hydroxylamine hydrochloride and sodium hydroxide is prepared, wherein the mixed solution has a mass ratio of hydroxylamine hydrochloride to sodium hydroxide of 1:0.5-1 and is dissolved in ethanol and deionized water; polyethyleneimine-acrylonitrile functionalized fiber is added thereto, and the reflux stirring conditions are 60-70° C. for 20-24 hours; after cooling to room temperature, the sample is taken out, washed with deionized water for several times, and dried at 50-60° C. overnight to obtain polyethyleneimine-amidoxime functionalized fiber.
5. The method for preparing the anti-adhesion uranium-extracting fiber according to claim 1, characterized in that: In step S4, trimethoxymercaptosilane coupling agent and isobornyl methacrylate are dissolved in ethanol, and then irradiated with ultraviolet light for 2-4 hours for grafting; then polyethyleneimine-amidoxime functionalized fiber is added thereto, Add an appropriate amount of ethanol and soak at room temperature for 10-12 hours; finally rinse with deionized water for several times, and then dry at 50-60°C for 20-24 hours to obtain the anti-adhesion uranium extraction fiber.
6. The method for preparing the anti-adhesion uranium-extracting fiber according to claim 1, characterized in that: In step S4, the mass ratio of trimethoxymercaptosilane coupling agent to isobornyl methacrylate is (1-3):
1.
7. The method for preparing the anti-adhesion uranium extracting fiber according to claim 1, characterized in that: In step S4, the mass ratio of polyethyleneimine-amidoxime functionalized fiber to isobornyl methacrylate is (0.5-3):
1.
8. An anti-adhesion uranium extraction fiber, characterized in that: The invention is prepared by the preparation method described in any one of claims 1 to 7.
9. A method for evaluating the antifouling performance of the anti-adhesion uranium extraction fiber prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The steps include: Using Diplophysarum as a model fouling organism to evaluate anti-fouling performance, the sample was sterilized under ultraviolet light; when the algae cell concentration in the culture medium entered a stable period, the sterilized sample was placed in the cell culture medium for mixed culture, and the original fiber algae solution was selected as a control sample. The algae solution was observed using a fluorescence microscope at different time periods; the anti-algae rate of the fiber was calculated as follows: Among them, A represents the number of seaweed attached to the fiber, N, M1 and M2 represent the number of seaweed attached to the fiber, the scale length and the fiber length, respectively; B represents the anti-algae rate, A1 and A2 represent the number of seaweed attached to the surface of modified fiber and HF, respectively.
10. A method for evaluating the uranium adsorption performance of the anti-adhesion uranium extraction fiber prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The steps include: The exponentially growing Amphiprion and Nitzschia closterium were added to simulated seawater containing uranium to obtain seawater containing algae liquid. The simulated seawater containing uranium was used as a control group for uranium adsorption experiments. Uranium adsorption experiments were carried out in seawater filtered with uranium and in unfiltered seawater.
